2011
DOI: 10.1007/s10457-011-9389-0
|View full text |Cite
|
Sign up to set email alerts
|

Migratory bird use of shade coffee: the role of structural and floristic features

Abstract: Shade coffee plantations support high numbers of Neotropical migratory birds, but relatively little is known about the structural and floristic attributes used by individual species. From 2005 to 2007, we studied the relationship between habitat characteristics and Neotropical migratory birds in shade coffee plantations in the Venezuelan Andes.Our results indicate that density of migrants was significantly related to both structural and floristic attributes of coffee farms. Specifically, upper canopy foragers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 45 publications
1
31
0
1
Order By: Relevance
“…At these elevations premontane forest has been extensively replaced by coffee plantations, as elsewhere in the Neotropics (Komar 2006, IDEAM 2010. Although shade-grown coffee can provide habitat for overwintering migratory birds (Tejeda-Cruz and Sutherland 2004, Komar 2006, Bakermans et al 2012, its value as stopover and premigratory fueling habitat, when energetic requirements are elevated, is unknown. In this paper, we (1) assess the relative quality of shade coffee and premontane forest as stopover habitat for two species of Nearctic-Neotropical migratory birds on spring migration in the Sierra Nevada de Santa Marta; (2) compare and contrast the ability of seven different measures to distinguish the relative quality of shade coffee and premontane forest at a stopover site in Colombia (Table 1); and (3) discuss the possible impact stopover-habitat use may have on the subsequent migratory strategy of birds in this important region.…”
Section: Introductionmentioning
confidence: 99%
“…At these elevations premontane forest has been extensively replaced by coffee plantations, as elsewhere in the Neotropics (Komar 2006, IDEAM 2010. Although shade-grown coffee can provide habitat for overwintering migratory birds (Tejeda-Cruz and Sutherland 2004, Komar 2006, Bakermans et al 2012, its value as stopover and premigratory fueling habitat, when energetic requirements are elevated, is unknown. In this paper, we (1) assess the relative quality of shade coffee and premontane forest as stopover habitat for two species of Nearctic-Neotropical migratory birds on spring migration in the Sierra Nevada de Santa Marta; (2) compare and contrast the ability of seven different measures to distinguish the relative quality of shade coffee and premontane forest at a stopover site in Colombia (Table 1); and (3) discuss the possible impact stopover-habitat use may have on the subsequent migratory strategy of birds in this important region.…”
Section: Introductionmentioning
confidence: 99%
“…We found that two foliage‐gleaners (Blackburnian and Cerulean warblers) attacked prey at the same rate, and all three foliage‐gleaners (Blackburnian, Cerulean, and Tennessee warblers) foraged in Inga more than expected based on availability. Bakermans et al () also noted that Cerulean Warblers exhibited a preference for foraging in Inga . During the non‐breeding season, Greenberg et al () found that three warblers in the Black‐throated Green Warbler ( Setophaga virens ) complex also attacked prey at the same rates, but found that these warblers differed in selection of foraging substrates (pine vs. oak).…”
Section: Discussionmentioning
confidence: 95%
“…Other researchers have found that flocking species with similar foraging behaviors forage at different heights in a variety of systems (Greenberg , Hutto , Eguchi et al , Greenberg et al ). Other investigators have also reported differences in foraging heights of male and female Cerulean Warblers, although whether this is a result of sexual segregation or other factors remains unknown (Bakermans et al , Muñoz and Colorado ). With their lower foraging height, Cerulean Warblers appeared to forage in shrubs and small trees more than the two other foliage‐gleaners and, interestingly, Cerulean Warblers were also most abundant at our two sites with small trees and shrubs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations